Integrating The Huyula Tradition into Contemporary Waqf Governance: A Study of Local Wisdom and Islamic Legal Reform - Nur Mohamad Kasim; Trubus Semiaji; Wahyudin Radjak; Hamdan Ladiku (KRTHA BHAYANGKARA, 2026)
This study examines the integration of the Huyula tradition, a local wisdom of the Gorontalo community, in contemporary waqf governance based on the principles of good governance and Islamic law reform. Huyula, which contains the values of togetherness, mutual cooperation, deliberation, and collective responsibility, has the potential to strengthen productive, transparent, and participatory waqf management, especially in the digital era with the use of technology such as e-waqf and blockchain. Through a pentahelix collaborative model involving government, society, academia, business, and the media, this tradition can become an institutional foundation responsive to modern socio-economic and technological challenges. This research uses mixed methods (Normative and Empirical), uses a qualitative approach and conducts interviews with 8 resource persons related to normative aspects and waqf management practices. The results of the study show that the revitalization of Huyula values can increase waqf literacy, nazhir capacity, and community participation in the planning, supervision, and evaluation of waqf, in line with the sustainable development goals (SDGs). Adaptive policies that accommodate local values in the national legal system and digital governance are recommended so that waqf management becomes more effective, equitable, and sustainable.